Semiautomatic Analysis on Computed Tomography in Locally Advanced or Metastatic Non-Small Cell Lung Cancer: Reproducibility and Prognostic Significance of Unidimensional and 3-dimensional Measurements. Issue 5 (September 2015) - Colombi, Davide; Manna, Carmelinda; Montermini, Ilaria; Seletti, Valeria; Diciotti, Stefano; Tiseo, Marcello; Fontana, Elisa; De Filippo, Massimo; Silva, Mario; Sverzellati, Nicola
Abstract : Purpose: The aim of the study was to compare both reproducibility and prognostic value of lesion size measurements obtained manually and semiautomatically on computed tomography in advanced non–small cell lung cancer (NSCLC). Materials and Methods: Manual axial longest diameter, semiautomatic axial longest diameter, and volume of NSCLC lesions were independently analyzed by 4 readers at baseline and after at least 1 cycle of platinum-based chemotherapy. The prognostic value of the proportional change in lesion size between baseline and follow-up CT was evaluated using either RECIST or experimental thresholds derived from the quartiles of the changes as assessed manually or semiautomatically. Results: Semiautomatic axial longest diameter (concordance correlation coefficient [CCC]: 0.980 to 0.987; variation coefficient [VC%]: 6% to 7.3%) and volume (CCC: 0.974 to 0.991; VC%: 5.6% to 9.5%) were more reproducible than manual axial longest diameter (CCC: 0.950 to 0.984; VC%: 6.4% to 11.7%). RECIST categories did not stratify patients with different survival durations. For 3/4 readers, a decrease of ⩽70% in lesion volume was associated with shorter survival (median survival: 11 mo, P <0.05; hazard ratio: 5 to 22.2, P <0.05). Conclusions: In advanced NSCLC, semiautomatic measures were more reproducible than manual diameter, and volumetric measurement may better predict patient survival. Abstract : Supplemental Digital Content is available in the text.